Rancang Bangun Game Edukasi Perjalanan Dang Hyang Nirartha di Bali - Ni Luh Candra Darmayanti; I Ketut Adi Purnawan; Putu Wira Buana (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2017)
Dang Hyang Nirartha is a prominent Hindu religious leader in the Indonesian archipelago. Dang Hyang Nirartha gave many changes to the archipelago of one of the island of Bali. Dang Hyang Nirartha provides many changes in the adaptation of the Hindu Religion concept to the existing culture in Bali. Dang Hyang Nirartha's Travel Educational Game in Bali was developed to educate people about Dang Hyang Nirartha's journey in Bali, given the importance of Dang Hyang Nirartha's role for the people of Bali. Dang Hyang Nirartha's Travel Educational Game in Bali was developed using the accelerometer method, so that later the user simply tilts the smartphone to move the character up, down, left and right to avoid the enemy and can finish the game. The resulting game is able to convey the learning about Dang Hyang Nirartha's journey in Bali through the information displayed on every stage and gameplay that describes Dang Hyang Nirartha's travel conditions in Bali.